Providing Evidence-based and Culturally Competent Care to Racial/ethnic Minority Young Adults with Anxiety Disorders: The Experience of an Urban Medical Center Clinic. Issue 2 (2nd April 2020) - Zerrate Parra, M. Carolina; Ortin, Ana; Erban, Rebecca; Reyes-Portillo, Jazmin; Schonfeld Reichel, Eva; Desai, Payal; Duarte, Cristiane S.
ABSTRACT: Anxiety disorders are the most common psychiatric disorder with onset in childhood, and the most prevalent in adulthood. Despite high prevalence, anxiety disorders are under-diagnosed and under-treated, particularly among racial/ethnic minority populations who are underserved while continuously facing multiple psychosocial stressors. Anxiety disorders can be highly impairing and can interfere with normal development, posing a threat to critical transitions in life such as the transition from adolescence to adulthood. Young adulthood is a crucial stage for intervention, as the brain is still developing, and attaining specific developmental milestones during this stage is essential to adequately navigate adult life. There is a lack of developmentally tailored, evidence-based, and culturally sensitive services for racial/ethnic minority young adults with anxiety disorders. This paper shares the experience of the Youth Anxiety Center Washington Heights Program (YAC-WH), a patient and culturally centered program developed for minority young adults in New York City experiencing anxiety disorders. We reference prior studies supporting the relevance of focusing on young adulthood, the use of cognitive-behavioral therapy as an evidence-based treatment in community settings, and the critical role of cultural competence. In addition, we delineate four types of barriers to treatment (developmental, clinical, ethnic background, psychosocial), commonly found in our patient population and describe the strategies utilized to overcome them. Our description demonstrates the feasibility of providing developmentally informed, evidence-based and culturally centered treatment to underserved racial/ethnic minority young adults.